Dimethylsulfoniopropionate Biosynthetic Bacteria in the Subseafloor Sediments of the South China Sea - Zhang, Yunhui; Sun, Kai; Sun, Chuang; Shi, Xiaochong; Todd, Jonathan D.; Zhang, Xiao-Hua (Frontiers in Microbiology, 2021)
Dimethylsulfoniopropionate (DMSP) is one of Earth’s most abundant organosulfur molecules, and bacteria in marine sediments have been considered significant producers. However, the vertical profiles of DMSP content and DMSP-producing bacteria in subseafloor sediment has not been described. Here we used culture-dependent and -independent methods to investigate microbial DMSP production and cycling potential in South China Sea (SCS) sediment. DMSP content in the SCS sediment was quantified in ten subseafloor sediment cores down to 8 m, decreasing from 11.25-20.90 nmol·g-1 in the surface to 0.56-2.08 nmol·g-1 in the bottom layers. Only few eukaryotic plastid sequences were found in sediment, supporting bacteria instead of algae as important sediment DMSP producers. Known bacterial DMSP biosynthesis genes (dsyB and mmtN) were only predicted to be in 0.0007-0.0195% of sediment bacteria, but novel DMSP-producing isolates with potentially unknown DMSP synthesis genes and/or pathways were identified in these sediments, including Marinobacter (Gammproteobacteria) and Erythrobacter (Alphaproteobacteria). The abundance of bacteria with the potential to produce DMSP decreased with sediment depth and such potential was extremely low at 690 cm depths. Bacterial DMSP catabolic genes were also most abundant in the surface oxic sediments with high DMSP concentrations. Furthermore, distinct DMSP-producing bacterial groups existed in surface and subseafloor sediment samples, and their abundance increased when samples were incubated under conditions known to enrich for DMSP producing bacteria. These results extend current knowledge on bacterial DMSP biosynthesis in marine sediments, implying DMSP biosynthesis process is not only confined to the surface oxic sediment zones and emphasizingemphasize the importance of future work to uncover the DMSP biosynthesis genes/pathways in novel DMSP-producing bacteria.